Knowledge, attitude and practice related to rabies among residents of Amhara region, Ethiopia - Bahiru, A.; Molla, W.; Yizengaw, L.; Mekonnen, S.A.; Jemberu, Wudu T. (Elsevier, 2022)
Background Rabies is an important viral zoonotic disease with high fatality rate and economic losses. The impact of rabies is considerably high in Asia and Africa. The study was designed to assess the community’s rabies knowledge, attitude and practice (KAP) and their determinants in Amhara region, Ethiopia.